3-D Quantum Transport Solver Based on the Perfectly Matched Layer and Spectral Element Methods for the Simulation of Semiconductor Nanodevices - Cheng, Candong (2007)
A 3-D quantum transport solver based on the spectral element method (SEM) and perfectly matched layer (PML) is introduced to solve the 3-D Schrödinger equation with a tensor effective mass. In this solver, the influence of the environment is replaced with the artificial PML open boundary extended beyond the contact regions of the device. These contact regions are treated as waveguides with known incident waves from waveguide mode solutions. As the transmitted wave function is treated as a total wave, there is no need to decompose it into waveguide modes, thus significantly simplifying the problem in comparison with conventional open boundary conditions. The spectral element method leads to an exponentially improving accuracy with the increase in the polynomial order and sampling points. The PML region can be designed such that less than −100 dB outgoing waves are reflected by this artificial material. The computational efficiency of the SEM solver is demonstrated by comparing the numerical and analytical results from waveguide and plane-wave examples, and its utility is illustrated by multiple-terminal devices and semiconductor nanotube devices.